If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11d + 1 = 6d Reorder the terms: 1 + 11d = 6d Solving 1 + 11d = 6d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-6d' to each side of the equation. 1 + 11d + -6d = 6d + -6d Combine like terms: 11d + -6d = 5d 1 + 5d = 6d + -6d Combine like terms: 6d + -6d = 0 1 + 5d = 0 Add '-1' to each side of the equation. 1 + -1 + 5d = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5d = 0 + -1 5d = 0 + -1 Combine like terms: 0 + -1 = -1 5d = -1 Divide each side by '5'. d = -0.2 Simplifying d = -0.2
| 8(2+3)x=4 | | 6x^5+11x^4-37x^3-33x^2+11x+6=0 | | 5(3a+3)=150 | | (5x-9)-(4x+6)=-12,5 | | 2(4w+5)+2w=80 | | 6a+6=-8 | | 5x+14=144-5x | | 5*m/3 | | 2z+x=69 | | 16-7=21 | | 3y-6=-11 | | 8x^2-800=0 | | 3n^2+7n-1000=0 | | 3n^2+7n+1000=0 | | 6+n=-4 | | 125x+150=-150-125x | | 20=z+7 | | 3x+9-2x+5=6x-4x+7 | | 20=-16t^2+32t+100 | | (c/3)+7=5+1/2 | | (2/3)(12-x)=4 | | 67537653764=8764875x | | smile=fun | | wel=ok | | oh=56 | | 56+5= | | 67+8x=5 | | 3+8x=4x-5 | | 7x+8x=5 | | 2*2x=5 | | y=-1.2x+2/3 | | 5x/x-3=8+15/x-3 |